Interrogating the Crucial Interactions at Play in the Chiral Cation-Directed Enantioselective Borylation of Arenes - Ermanis, Kristaps; Gibson, David C.; Genov, Georgi R.; Phipps, Robert J. (ACS catalysis, 2023)
Rendering a common ligand scaffold anionic and then pairing it with a chiral cation represents an alternative strategy for developing enantioselective versions of challenging transformations, as has been recently demonstrated in the enantioselective borylation of arenes using a quinine-derived chiral cation. A significant barrier to the further generalization of this approach is the lack of understanding of the specific interactions involved between the cation, ligand, and substrate, given the complexity of the system. We have embarked on a detailed computational study probing the mechanism, the key noncovalent interactions involved, and potential origin of selectivity for the desymmetrizing borylation of two distinct classes of substrate. We describe a deconstructive, stepwise approach to tackling this complex challenge, which involves building up a detailed understanding of the pairwise components of the nominally three component system before combining together into the full 263-atom reactive complex. This approach has revealed substantial differences in the noncovalent interactions occurring at the stereodetermining transition state for C–H oxidative addition to iridium for the two substrate classes. Each substrate engages in a unique mixture of diverse interactions, a testament to the rich and privileged structure of the cinchona alkaloid-derived chiral cations. Throughout the study, experimental support is provided, and this culminates in the discovery that prochiral phosphine oxide substrates, lacking hydrogen bond donor functionality, can also give very encouraging levels of enantioselectivity, potentially through direct interactions with the chiral cation. We envisage that the findings in this study will spur further developments in using chiral cations as controllers in asymmetric transition-metal catalysis.